1976
DOI: 10.1007/bf01073036
|View full text |Cite
|
Sign up to set email alerts
|

Myxedema ascites

Abstract: A 74-year-old man presented with mental obtundation and massive ascites without evidence of significant impairment of liver function. Thyroid function studies suggested hypothyroidism. Aspirated ascitic fluid had the characteristics of an exudate. Thyroid replacement therapy resulted in rapid clinical improvement with resolution of the ascites. Prompt recognition of myxedema ascites may prevent the inappropriate use of diuretic agents, therapeutic paracentesis, and sometimes unnecessary laparotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Review of literature revealed 52 documented cases of myxedema ascites in adults. [4589] A very consistent finding was high total protein level (>2.5 g/dl) in almost all cases with mean SAAG of 1.5 g/dl with a range of 0.8-2.3 g/dl. [1] WBC counts were rather low, usually with a lymphocytic predominance with a mean of 60 cells/μl and 81% lymphocytes.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Review of literature revealed 52 documented cases of myxedema ascites in adults. [4589] A very consistent finding was high total protein level (>2.5 g/dl) in almost all cases with mean SAAG of 1.5 g/dl with a range of 0.8-2.3 g/dl. [1] WBC counts were rather low, usually with a lymphocytic predominance with a mean of 60 cells/μl and 81% lymphocytes.…”
Section: Discussionmentioning
confidence: 71%
“…Prompt recognition of hypothyroid ascites prevents the inappropriate use of diuretics and unnecessary procedures, including repeated paracenteses and liver biopsies. [8]…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature turned up 51 well-documented cases of myxedema ascites (Table 1) (2,3,7,8,10-20). A very consistent finding was the high total protein level (>2.5 g/dL) (7).…”
Section: Discussionmentioning
confidence: 99%
“…There was usually a significant delay in the diagnosis, with a mean of eight months. Prompt recognition of myxedema ascites prevents the inappropriate use of diuretics and unnecessary procedures, including repeated paracenteses, liver biopsies and exploratory laparotomies (10). A constant feature was the good response to thyroid hormone replacement therapy, which led to elimination of the ascites in every instance.…”
Section: Discussionmentioning
confidence: 99%